Deciphering the Worlds of Hebrews : Collected Essays - Gelardini, Gabriella, (Novum Testamentum, Supplements ;, 2021)
In the collection entitled Deciphering the Worlds of Hebrews Gabriella Gelardini gathers fifteen essays written in the last fifteen years, twelve of which are in English and three in German. Arranged in three parts (the world of , behind , and in front of Hebrews's text), her articles deal with such topics as structure and intertext, sin and faith, atonement and cult, as well as space and resistance. She reads Hebrews no longer as the enigmatic and homeless outsider within the New Testament corpus, as the "Melchizedekian being without genealogy"; rather, she reads Hebrews as one whose origin has finally been rediscovered, namely in Second Temple Judaism.